PERANCANGAN DAN IMPLEMENTASI APLIKASI KEUANGAN DENGAN MENERAPKAN METODE RASIO KEUANGAN SEBAGAI PENGUKUR KINERJA PERUSAHAAN (STUDI KASUS DI PT. GARDA AGATA NUSANTARA) - COMPUTING INFORMATIKA; yusuf Muharam; Neneng Reka Meisa (COMPUTING | Jurnal Informatika, 2022)
ABSTRACT : This research is motivated by the problems and constraints on the financial statements that run at PT. Garda Agata Nusantara is in the form of data validation that has not been properly integrated, has not displayed reports on financial ratios, balance sheets and profit/loss, as well as financial applications that cannot be accessed remotely and are limited by time. The purpose of this research is to provide a system that can present accurate company financial performance reports and can be accessed easily from anywhere and anytime. By using a qualitative method approach and the SDLC waterfall development model in application design through stages including the system model design in this study using UML (Unified Modeling Language). Based on the results of analysis, design, and testing using the black-box testing method. The results of this study are financial applications by applying the financial ratio method are expected to help the company to determine the company's financial position in a certain period, find out the success and weaknesses of the company and can find out steps to improve the company's management performance next.